Patients’ transition in the intensive care Units : concept analysis - Mohamed Ludin, Salizar; Arbon, Paul; Parker, Steve (Elsvier Ltd, 2013)
Background: Adequate preparation of critically ill patients throughout their transition experience within and following discharge from the Intensive Care Unit is an important element of the nursing care process during critical illness. However, little is known about nurses’ perspectives of, and engagement in, caring for critically ill patients during their transition experiences. Aim: This paper aims to review the literature about the concept of transition within the context of critically ill patients in the Intensive Care Unit, focusing on Intensive Care Unit nurses. Review method: CINAHL, MEDLINE, OVID, Science Direct, SAGE eReference and SAGE Journal Online data bases were searched for relevant literature published since 1970. Results: The critically ill patients’ transitions in Intensive Care Units are generally described as a period of transfer or change of situation, or the experience of inner change or role during and after the illness. The critically ill patients’ transition experience per se is not directly described, nor is nurses’ understanding of it. Conclusion: Nurses’ understanding of critically ill patients’ transition may significantly impact the patients’ care in the Intensive Care Unit. Thus, research is needed that focuses more on evaluating nurses’ understanding of patients’ transition and its consequences. © 2013 Elsevier Ltd. All rights reserved.